«Intrapsychic interview» in healthy and patients with depressive disorders - S. V. Kharitonov; V. P. Zaitsev; V. M. Golubev; A. A. Kukshina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article presents the results of a study on the application possibilities developed by the authors method of «intrapsychic interview» carried out in the structure of the psychiatric examination of patients with depressive episodes of moderate and mild degree. In the comparison group were healthy individuals, who were also conducting «intrapsychic interview». The study involved 64 patients with an established diagnosis of depressive episode (F31.3, F32.0, F32.1) and 23 healthy mental attitude of a person. The study revealed that patients with depressive symptoms experience mental phenomena is characterized by the tendency to avoid experiencing negative feelings, the desire to achieve a state of «inner peace», a tendency to postpone the satisfaction of natural needs, a decline in the ability to recognize their own feelings and their interpretation. According to the study it is assumed that the «intrapsychic interview» allows you to achieve a more complete understanding of the clinical picture of mental disorders and their dynamics.